2023
DOI: 10.22462/01.01.2023.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperbaric oxygen therapy on periodontal disease: a literature review

Abstract: Background and objective: Hyperbaric oxygen (HBO2) has been the subject of research in many areas of dentistry. HBO2 seems to be a useable, additional treatment method. However, there are still no certain conclusions and clear guidelines for procedures. The aim of the study was to collect current literature assessing the use of hyperbaric oxygen therapy in the treatment of periodontitis. Materials and Methods: The following review was performed using medical databases Medline via PubMed and Google Scholar. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Only a statistically greater reduction was obtained for (p < 0.05) BOP in the study group compared to the control group. The authors concluded that HBO therapy in combination with subgingival mechanotherapy can be an effective treatment for moderate to severe forms of periodontitis [26]. A study by Mulawarmanti et al (2019) in animals with diabetes and periodontitis showed a statistically significant reduction in IL-1β expression and an increase in IL-10 expression after treatment with HBO and HBO in combination with 3% Stichopus hermanii gel [27].…”
Section: Hyperbaric Oxygen Therapy-study Rewievmentioning
confidence: 99%
“…Only a statistically greater reduction was obtained for (p < 0.05) BOP in the study group compared to the control group. The authors concluded that HBO therapy in combination with subgingival mechanotherapy can be an effective treatment for moderate to severe forms of periodontitis [26]. A study by Mulawarmanti et al (2019) in animals with diabetes and periodontitis showed a statistically significant reduction in IL-1β expression and an increase in IL-10 expression after treatment with HBO and HBO in combination with 3% Stichopus hermanii gel [27].…”
Section: Hyperbaric Oxygen Therapy-study Rewievmentioning
confidence: 99%